A method for preparing a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron using methionine
By using methionine and iron salt to form complexes in carbon-based catalysts, a catalyst co-doped sulfur, nitrogen and single-atom iron is prepared, which solves the high efficiency, stability and stability of existing non-platinum ORR catalysts. The cost deficiency has achieved high activity and stability of oxygen reduction catalytic effect.
Patent Information
- Application Number
- CN202111264551.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-10-28
AI Technical Summary
Existing non-platinum oxygen reduction reaction (ORR) catalysts have shortcomings in terms of efficiency, stability and cost, especially in large-scale commercial applications.
By using methionine and iron salt to form a complex, a carbon-based catalyst co-doped sulfur, nitrogen and single-atom iron was prepared, achieving high activity and stability of the catalyst.
The prepared catalyst exhibits oxygen reduction catalytic activity and stability better than 20% commercial platinum carbon catalyst under alkaline conditions, and the preparation process is simple and low cost.
Smart Images

Figure CN114188550B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy catalyst materials, and in particular relates to a method for preparing a sulfur, nitrogen and single-atom iron co-doped carbon-based catalyst by utilizing methionine. Background Art
[0002] As new energy conversion and storage devices that have attracted much attention, the theoretical research and technological development of fuel cells and metal-air batteries have attracted the interest of more and more scientists. However, as the core reaction of electrochemical energy conversion and storage systems, the sluggish kinetics of the oxygen reduction reaction (ORR) hinders the overall energy conversion efficiency and the large-scale commercial application of new technologies. Platinum-based catalysts are considered to be the most ideal ORR catalysts. However, due to the high price and scarce reserves of platinum metal, the high cost has become one of the most important factors hindering the development of proton exchange membrane fuel cells (PEMFCs) and metal-air batteries. Therefore, the research and development of efficient, stable and inexpensive non-platinum ORR catalysts has become the key to breaking through related technologies.
[0003] Among all non-precious metal catalysts, transition metal and nitrogen co-doped carbon-based catalysts (MNCs) with porphyrin-like structures have become the most important type of non-precious metal catalysts due to their cheap and readily available raw materials and oxygen reduction activity that is almost comparable to that of platinum. In particular, when transition metal elements are distributed in the catalyst in the form of single atoms, isolated metal atoms are anchored on the carbon support through the coordination of surrounding atoms (nitrogen, phosphorus and other elements). Because the utilization rate of metal atoms as active sites is close to 100%, their activity far exceeds that of traditional catalysts in which transition metals are distributed in the form of nanoparticles. In addition, it has been found that by incorporating heteroatoms with different electronegativity, such as phosphorus, sulfur, selenium and other elements, the electronic structure of the active center is changed, thereby achieving the effect of regulating the activity and selectivity of the catalyst. Therefore, exploring the preparation of MNC catalysts in which transition metal elements are distributed in the form of single atoms and doped with multiple non-metallic elements at the same time is of great significance for the large-scale application of carbon-based catalysts.
[0004] Chinese patent CN108686693 A reported a sulfur, nitrogen and single-atom cobalt co-doped carbon-based catalyst and its preparation method. They used a ball mill to evenly mix the cobalt source, sulfur source and nitrogen source to obtain a catalyst precursor. After the precursor was pyrolyzed, a sulfur and nitrogen co-doped single-atom cobalt catalyst was obtained. The catalyst showed good activity. However, the catalyst prepared by this method using glucose as the carbon source does not have a regular morphology;
[0005] Chinese patent CN104998673 A reported a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom transition metal and its preparation method. They used a method of mixing a copolymer of tripyrrole-[1,3,5]-triazine and thiophene with a non-precious metal salt to obtain a carbon-based catalyst with good activity. However, the preparation method of the catalyst involves the use of Friedel-Crafts reaction to synthesize the copolymer, and the steps are too complicated and cumbersome.
[0006] In view of the shortcomings of the related technologies, the present invention proposes a simple and inexpensive preparation technology for preparing carbon-based catalysts co-doped with multiple non-metallic elements and single transition metal atoms, and successfully prepares carbon-based catalysts co-doped with sulfur, nitrogen and single-atom iron, which have regular morphology, high specific surface area and simple synthesis method. Summary of the invention
[0007] The purpose of the present invention is to improve the oxygen reduction activity and stability of iron-nitrogen-carbon catalysts, and a method for preparing sulfur-nitrogen co-doped iron single-atom catalysts using methionine is proposed. The prepared material shows a significant performance improvement compared to the sulfur-free catalyst. Under alkaline conditions, the oxygen reduction catalytic performance of the catalyst is better than 20% of commercial platinum-carbon catalysts.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron using methionine, comprising the following steps:
[0010] (1) The carbon powder obtained by thermal cracking of ZIF-8 is washed with dilute acid, and then vacuum filtered and dried to obtain a porous carbon material;
[0011] (2) dissolving the porous carbon material, methionine and iron salt of step (1) in deionized water, adjusting the temperature and pH value of the reaction system so that the two react to form a complex of methionine and iron ions, thereby obtaining a solution of methionine iron complex;
[0012] (3) After the solution in step (2) is fully stirred, the mixture is evaporated to dryness in a water bath to obtain a carbon powder precursor adsorbed with the methionine iron complex;
[0013] (4) The carbon powder precursor obtained in step (3) is ground uniformly and then thermally cracked in an inert atmosphere. The cracking product is naturally cooled, acid-washed, and then subjected to a secondary heat treatment in an inert atmosphere to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron.
[0014] Furthermore, in step (2), the iron salt includes one of ferric sulfate, ferric nitrate, ferric perchlorate, ferric phosphate, ferric pyrophosphate, ferric chloride, ferric bromide, ferric acetate, ammonium ferric citrate, ferrous sulfate, ferrous perchlorate, ferrous phosphate, ferrous chloride, ammonium ferrous sulfate, ferrous gluconate, and ferrous iodide.
[0015] Furthermore, in step (1), the temperature of the dilute acid pickling is 80°C; the temperature of the ZIF-8 thermal cracking is 600°C-1000°C, and the time is 1-5h.
[0016] Furthermore, in step (2), the temperature of the system in which methionine and iron salt are complexed is 60°C-100°C.
[0017] Furthermore, in step (2), the pH of the system in which methionine and iron salt are complexed is 3.4-7.4; and the relative mass ratio of methionine: iron salt: carbon powder in the catalyst is 3:2:1, 1:1:1, 2:2:1 or 2:1:1.
[0018] Furthermore, in step (3), the evaporation temperature of the carbon powder precursor adsorbed with the methionine iron complex is 60° C.-100° C., and the evaporation time is 10 h-24 h.
[0019] Furthermore, in step (4), the gas used in the inert atmosphere for high-temperature pyrolysis is argon or nitrogen.
[0020] Furthermore, in step (4), the temperature of the first pyrolysis and the second heat treatment of the precursor are both 600-1000°C, and the time is 1-5 hours.
[0021] Furthermore, in step (4), the pickling time is 8h-24h, and the pickling is performed using dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid or dilute perchloric acid with a concentration of 0.01-1 mol / L.
[0022] The present invention realizes single-atom doping of Fe in carbon-based catalysts by using a method of generating a complex with methionine and iron salts, and simultaneously realizes co-doping of N and S elements, which greatly improves the catalytic activity and stability of such catalysts for oxygen reduction processes. This method provides a new idea for the research and development of high-activity, low-cost non-precious metal oxygen reduction catalysts, and is of great significance for solving the current problems of doped carbon-based catalysts and promoting the development and practical application of such catalysts.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] (1) The raw materials are cheap and easily available, the preparation process is simple, the equipment requirements are low, and the reaction conditions are easy to control and master.
[0025] (2) The use of ZIF-8 with a regular dodecahedral structure as a precursor ensures that the catalyst has a regular morphology after pyrolysis.
[0026] (3) Through the formation of methionine iron complex, the coordination structure of sulfur, nitrogen, and iron atoms in the complex is maintained in the porphyrin-like structure of the carbon material after pyrolysis, achieving precise doping of sulfur and nitrogen elements relative to the active sites of the iron unit.
[0027] (4) We have successfully prepared a highly active carbon-based catalyst co-doped with S, N and single-atom iron. Its activity is much higher than that of the Fe / N / C catalyst not co-doped with S. Under alkaline conditions, its oxygen reduction catalytic activity and stability are better than those of the commercial Pt / C catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an infrared spectrum of the carbon powder adsorbing methionine iron complex prepared in Example 3 of the present invention;
[0029] Figure 2 This is the XRD spectrum of the material prepared in Example 3 of the present invention;
[0030] Figure 3 This is a comparison of the linear sweep voltammetric curve of the material prepared in Example 3 of the present invention under alkaline conditions with that of a 20% commercial platinum-carbon catalyst;
[0031] Figure 4 This is a comparison of the time-current curve of the material prepared in Example 3 of the present invention under alkaline conditions with that of a 20% commercial platinum-carbon catalyst;
[0032] Figure 5 Scanning electron microscope image of the carbon-based catalyst. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0034] A method for preparing a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron using methionine, comprising the following steps:
[0035] (1) Preparation of nitrogen-doped porous carbon supports
[0036] The pyrolysis carbon powder obtained by thermal cracking ZIF-8 at 600°C-1000°C in a nitrogen or argon atmosphere is pickled in a dilute acid with a concentration of 0.01-1 mmol / L for 8-24 hours, and then vacuum filtered and vacuum dried to obtain a nitrogen-doped porous carbon material;
[0037] The dilute acid is one of hydrochloric acid, sulfuric acid, nitric acid, and perchloric acid.
[0038] (2) Preparation of an aqueous solution containing methionine iron complex
[0039] Weigh a certain amount of methionine, iron salt and the carbon powder in step (1) and add them to deionized water for reaction, adjust the temperature of the reaction system to 60-100° C. and the pH value to 3.4-7.4, so that the two react to form a complex of methionine and iron ions, thereby obtaining a methionine iron complex solution;
[0040] Methionine, iron salt, and carbon powder, the mass ratios are 3:2:1, 1:1:1, 2:2:1, and 2:1:1.
[0041] The iron salt is one of ferric sulfate, ferric nitrate, ferric perchlorate, ferric phosphate, ferric pyrophosphate, ferric chloride, ferric bromide, ferric acetate, ammonium ferric citrate, ferrous sulfate, ferrous perchlorate, ferrous phosphate, ferrous chloride, ferrous sulfate ammonium, ferrous gluconate, and ferrous iodide.
[0042] (3) Preparation of carbon materials adsorbed with methionine iron complex
[0043] After the solution in step (2) is fully stirred, it is evaporated to dryness in a water bath at 60-100°C for 10-24 hours, and the mixture is evaporated to dryness to obtain a carbon powder precursor adsorbing methionine iron complex.
[0044] (4) Preparation of carbon-based catalysts co-doped with sulfur, nitrogen and single-atom iron
[0045] The carbon powder precursor obtained in step (3) is ground evenly and then calcined at 600°C-1000°C in a nitrogen or argon atmosphere. The cracking product is naturally cooled, acid-washed and subjected to secondary pyrolysis in a nitrogen or argon atmosphere to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron.
[0046] Example 1
[0047] (1) The pyrolysis carbon powder obtained by thermal cracking ZIF-8 at 1000°C in a nitrogen atmosphere was acid-washed in 0.5 mmol / L dilute hydrochloric acid for 8 h, and then vacuum-filtered and vacuum-dried to obtain a nitrogen-doped porous carbon material;
[0048] (2) adding 100 mg of the porous carbon material obtained in step (1), 300 mg of methionine and 200 mg of ferric chloride into deionized water, adjusting the temperature of the reaction system to 60° C. and the pH value to 3.4, and stirring the mixture to allow the two to react to form a complex solution of methionine and iron ions;
[0049] (3) After fully stirring the solution in step (2), the solution was evaporated to dryness at 60° C. for 10 h to obtain a carbon powder precursor adsorbing the methionine iron complex;
[0050] (4) Grinding the carbon powder precursor obtained in step (3) uniformly, calcining at 750° C. for 2 h in a nitrogen atmosphere, cooling naturally, and then washing with 0.5 mmol / L dilute hydrochloric acid and performing secondary pyrolysis to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron;
[0051] The Fe-NS-C oxygen reduction catalyst prepared in this example was electrochemically tested in 0.1M KOH electrolyte, and its oxygen reduction half-wave was around 0.84V vs. RHE.
[0052] Example 2
[0053] (1) The pyrolysis carbon powder obtained by thermal cracking ZIF-8 at 900°C in a nitrogen atmosphere was acid-washed in 1 mmol / L dilute sulfuric acid for 10 h, and then vacuum-filtered and vacuum-dried to obtain a nitrogen-doped porous carbon material;
[0054] (2) dissolving 100 mg of the porous carbon material obtained in step (1), 100 mg of methionine and 100 mg of ferrous sulfate in deionized water for reaction, adjusting the temperature of the reaction system to 100° C. and the pH value of the system to 7.4, so that the two react to form a complex of methionine and iron ions, and after a period of time, obtaining a solution containing a methionine iron complex;
[0055] (3) After the solution in step (2) is fully stirred, it is evaporated to dryness at 80° C. for 18 h to obtain a carbon powder precursor adsorbing the methionine iron complex.
[0056] (4) The carbon powder precursor obtained in step (3) was ground evenly, calcined at 800°C for 3 h in a nitrogen atmosphere, cooled naturally, and then washed with 1 mmol / L dilute sulfuric acid and subjected to secondary pyrolysis to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron.
[0057] The Fe-NS-C oxygen reduction catalyst prepared in this example was electrochemically tested in 0.1M KOH electrolyte, and its oxygen reduction half-wave was around 0.87V vs. RHE.
[0058] Example 3
[0059] (1) The pyrolysis carbon powder obtained by thermal cracking ZIF-8 at 900°C in a nitrogen atmosphere was washed with 0.1 mmol / L dilute nitric acid for 12 h, and then vacuum filtered and dried to obtain a nitrogen-doped porous carbon material;
[0060] (2) dissolving 100 mg of the porous carbon material obtained in step (1), 200 mg of methionine and 200 mg of ferrous gluconate in deionized water for reaction, adjusting the temperature of the reaction system to 80° C. and the pH value of the system to 6.4, so that the two react to form a complex of methionine and iron ions, and after a period of time, obtaining a solution containing a methionine iron complex;
[0061] (3) After the solution in step (2) is fully stirred, the mixed system is evaporated to dryness at 100° C. for 10 h to obtain a carbon powder precursor adsorbing the methionine iron complex.
[0062] Figure 1 This is the infrared spectrum of the carbon powder precursor, 3021 and 2919 cm -1 Vas(NH 2 ) and Vs(NH 2 ) absorption peak, indicating the coordination of amino group with iron ion; 618cm -1 is the V(Fe-N) absorption peak, 438cm-1 is the V(Fe-O) absorption peak, and the appearance of these three absorption peaks indicates that the methionine iron complex has been successfully synthesized.
[0063] (4) The carbon powder precursor obtained in step (3) was ground evenly, calcined at 950° C. for 1 h in a nitrogen atmosphere, cooled naturally, and then washed with 0.1 mmol / L dilute nitric acid and subjected to secondary pyrolysis to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single atoms.
[0064] Figure 2 The XRD pattern of the carbon-based catalyst shows only C (002) and C (101) diffraction peaks but no diffraction peaks of the iron aggregate phase, indicating that the iron element does not exist in the catalyst in the form of an aggregate phase.
[0065] Figure 3 Linear sweep voltammetry (LSV) test of carbon-based catalyst and 20% Pt / C catalyst. The Fe-NS-C oxygen reduction catalyst prepared in this example was electrochemically tested in 0.1M KOH electrolyte, and its oxygen reduction half-wave was about 0.895V vs. RHE, which was 45mV higher than the half-wave potential of 20% Pt / C 0.850 V vs. RHE. This shows that the catalytic activity of the prepared carbon-based catalyst is higher than that of the 20% Pt / C catalyst.
[0066] Figure 4 The time-current curve of the carbon-based catalyst and the 20% Pt / C catalyst. The test environment is alkaline, oxygen environment, and the rotation speed is 900rpm. After 20,000s of testing, the current retention rate of the carbon-based catalyst is 92.5%, and the current retention rate of the 20% Pt / C catalyst is 90.3%. This shows that the stability of the carbon-based catalyst is higher than that of the 20% Pt / C catalyst.
[0067] Figure 5 This is a scanning electron microscope image (SEM) of a carbon-based catalyst. As can be seen from the figure, the prepared catalyst has a relatively regular geometric morphology.
[0068] Example 4
[0069] (1) The pyrolysis carbon powder obtained by thermal cracking ZIF-8 at 850°C in a nitrogen atmosphere was acid-washed in 0.3 mmol / L dilute perchloric acid for 20 h, and then vacuum-filtered and vacuum-dried to obtain a nitrogen-doped porous carbon material;
[0070] (2) dissolving 100 mg of the porous carbon material obtained in step (1), 200 mg of methionine and 100 mg of ferric sulfate in deionized water for reaction, adjusting the temperature of the reaction system to 100° C. and the pH value of the system to 5.4, so that the two react to form a complex of methionine and iron ions, and after a period of time, a solution containing a methionine iron complex is obtained;
[0071] (3) After the solution in step (2) is fully stirred, the mixed system is evaporated to dryness at 70° C. for 14 h to obtain a carbon powder precursor adsorbing the methionine iron complex.
[0072] (4) The carbon powder precursor obtained in step (3) was ground uniformly, calcined at 850°C for 4 h in an argon atmosphere, cooled naturally, and then washed with 0.3 mmol / L dilute perchloric acid and subjected to secondary pyrolysis to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron.
[0073] The Fe-NS-C oxygen reduction catalyst prepared in this example was electrochemically tested in 0.1M KOH electrolyte, and its oxygen reduction half-wave was around 0.865V vs RHE.
[0074] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron using methionine, characterized in that: The following steps are involved: (1) The carbon powder obtained by thermal cracking of ZIF-8 is acid-washed, vacuum-filtered, and vacuum-dried to obtain a porous carbon material; (2) dissolving the porous carbon material, methionine and iron salt of step (1) in deionized water, adjusting the temperature and pH value of the reaction system so that the two react to form a complex of methionine and iron ions, thereby obtaining a solution of methionine iron complex; (3) After the solution in step (2) is fully stirred, the mixture is evaporated to dryness in a water bath to obtain a carbon powder precursor adsorbed with the methionine iron complex; (4) grinding the carbon powder precursor obtained in step (3) uniformly, and then thermally cracking it in an inert atmosphere. After the cracking product is naturally cooled, it is acid-washed and then subjected to a secondary heat treatment in an inert atmosphere to obtain a carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron; In step (2), the iron salt includes one of ferric sulfate, ferric nitrate, ferric perchlorate, ferric phosphate, ferric pyrophosphate, ferric chloride, ferric bromide, ferric acetate, ammonium ferric citrate, ferrous sulfate, ferrous perchlorate, ferrous phosphate, ferrous chloride, ammonium ferrous sulfate, ferrous gluconate, and ferrous iodide; In step (1), the pickling temperature is 80°C; the ZIF-8 thermal cracking temperature is 600°C-1000°C, and the time is 1-5h; In step (2), the temperature of the system in which methionine and iron salt are complexed is 60°C-100°C; In step (2), the pH of the system in which methionine and iron salt are complexed is 3.4-7.4; the relative mass ratio of methionine: iron salt: porous carbon material in the catalyst is: 3:2:1, 1:1:1, 2:2:1 or 2:1:1; In step (3), the evaporation temperature of the carbon powder precursor adsorbed with the methionine iron complex is 60° C.-100° C., and the evaporation time is 10 h-24 h; In step (4), the gas used in the inert atmosphere for high-temperature pyrolysis is argon or nitrogen; In step (4), the temperature of the first thermal cracking and the second thermal treatment of the precursor are both 600-1000° C. and the time is 1-5 h; In step (4), the pickling time is 8h-24h, and the pickling is carried out using dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid or dilute perchloric acid with a concentration of 0.01-1 mol / L.
2. A carbon-based catalyst co-doped with sulfur, nitrogen and single-atom iron is prepared by the preparation method described in claim 1 using methionine.
Citation Information
Patent Citations
Nitrogen and sulfur co-doped carbon-loaded non-noble metal type oxygen reduction catalyst and preparation method thereof
CN104998673A
Preparation method of mono-atomic cobalt based nitrogen-sulfur dually-doped carbon material catalyst
CN108686693A